1990
DOI: 10.1093/ageing/19.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control in Elderly Subjects

Abstract: The postural stability of 23 subjects aged 85 years or over was studied with a force platform. The sensory function of the lower limbs was disturbed with small vibrators placed on both calf muscles and/or by placing the subjects on a platform covered with foam plastic. When compared with a group (n = 100) of 50-60-year-old subjects, the elderly subjects had significantly higher sway velocities even during nonperturbed conditions. The perturbation of muscle spindles with vibration and/or pressoreceptor function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(126 citation statements)
references
References 0 publications
6
116
0
4
Order By: Relevance
“…Sensory deficits in the lower extremity, visual impairment, and vestibular impairment contribute significantly to poor postural control in the elderly. [26][27][28][29][30] The case is worse with elderly people with diabetes because the disease can affect the central and peripheral nervous systems, vestibular system, and vision, resulting in poor sensory input and limited central processing of the information received by the brain leading to poor body balance. 10,31,32 Defects in body balance result in increased body sway, decreased postural stability, and increased incidence of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory deficits in the lower extremity, visual impairment, and vestibular impairment contribute significantly to poor postural control in the elderly. [26][27][28][29][30] The case is worse with elderly people with diabetes because the disease can affect the central and peripheral nervous systems, vestibular system, and vision, resulting in poor sensory input and limited central processing of the information received by the brain leading to poor body balance. 10,31,32 Defects in body balance result in increased body sway, decreased postural stability, and increased incidence of falls.…”
Section: Discussionmentioning
confidence: 99%
“…These sensory systems are further controlled by the central nervous systems located in the spinal cord, the brainstem, basal ganglia, cerebellum and cerebral cortex (Horak 1997). Vestibular input governs typically 65% of the body sway during sudden perturbation in standing, while 35% is accounted for by visual, proprioceptive and other input (Pyykkö et al 1990).…”
Section: Postural and Balance Controlmentioning
confidence: 99%
“…The COM-COP difference, on the contrary, has been reported to be proportional to the horizontal component of the ground reaction force captured by plantar cutaneous receptors located in the foot sole (Morasso et al 1999). Following latencies in muscle activation after tripping and slipping perturbations have been reported: 120 -200 ms for visual control and 60 -140 ms for proprioceptive control (Pyykkö et al 1990, Eng et al 1994, Tang et al 1998. However, other studies have claimed that a stiffness control may act almost immediately as the ankle joint angle is changed, causing the COP to move in the same direction as the COM (Winter et al 1998, cf.…”
Section: Postural and Balance Controlmentioning
confidence: 99%
“…Proprioceptive input from the muscles of the legs and trunk plays an important role in maintaining postural stability [34]. Previous studies have reported that proprioception and vibration sensation in the lower limbs decrease during normal aging [3,4] and also reported that postural instability has been observed in elderly people [35]. Therefore, a vibratory stimulus that matches the response frequency of the receptors present in skeletal muscle may influence body sway (Figure 6).…”
Section: Sensory Proprioceptive Inputs In Postural Controlmentioning
confidence: 99%